A INVESTIGATING EFL LEARNERS' INSTRUMENTAL MOTIVATION IN LEARNING ENGLISH - Nia Noviana; Mutiara Ayu (Universitas Teknokrat Indonesia, 2022)
Motivation is something that encourages someone's willingness to do something to achieve what they want. In this study, the motivation in question is motivation in the field of language learning, especially learning English. This study aims to discuss what kinds of instrumental motivation are encouraging students in learning English. In conducting this study, the researcher used Descriptive Qualitative Method. The data collecting technique used in this study was to conduct a survey using Google Form 'Questions (questionnaire) with the number of questions in the Google Form are six questionnaires with four answer choices (Strongly Agree, Agree, Disagree, Strongly Disagree). The subjects of the research are coming from the students of English Education major in Universitas Teknokrat Indonesia, especially students from PI18A class. The object of this research is students' perceptions about what kind of instrumental motivations that motivate them and how high the motivation they have when learning English. The results of the study indicate that the majority of participants have high instrumental motivation in learning English.